How organisations generate and use customer insight - Said, Emanuel; Macdonald, Emma K.; Wilson, Hugh (Taylor & Francis, 2015)
The generation and use of customer insight in marketing decisions is poorly understood, partly due to difficulties in obtaining research access and partly because market-based learning theory views knowledge as a fixed asset. However, customer insight takes many forms, arrives at the organisation from increasingly diverse sources and requires more than mere dissemination if it is to be useful. A multiple case study approach is used to explore managerial practices for insight generation and use. Multiple informants from each of four organisations in diverse sectors were interviewed. Findings reveal the importance of value alignment and value monitoring across the insight demand chain, to complement the information processing emphasis of extant research. Within the firm, the study suggests the importance of customer insight conduct practices including insight format, the role of automation and insight shepherding, to complement the much-researched process perspective. The study provides a basis for assessing the effectiveness of insight processes by both practitioners and scholars.
Keywords: Business to business marketing; Customer insight; Market based learning; Market research; Case study